Hydrocarbon potential of Late Palaeozoic residual basins in the Central Asian Orogenic Belt: Insights from the tectonic evolution of the Yinggen‐Ejinaqi Basin, Inner Mongolia, China. (18th December 2019) - Abitkazy, Taskyn; Ma, Yongsheng; Shi, Kaibo; Wu, Shuhong; Mu, Langfeng; Zhao, Lisha; Liu, Bo
Abstract : The Yinggen‐Ejinaqi Basin (YEB) is located in the central‐southern part of the Central Asian Orogenic Belt (CAOB). Tectonically, the basin is situated at the intersection between the eastern and western CAOB, where Late Palaeozoic strata were well exposed. Hence, it offers a great opportunity to study the deep strata of the eastern CAOB. In this paper, based on extensive studies of Upper Palaeozoic field outcrops and reanalysis of associated geochemical and geochronological data in previous research, the local stratigraphic correlation is established, and the tectonic evolution, sedimentary filling, sedimentary characteristics, and petroleum system of the YEB are discussed. It is revealed that: (a) The filling characteristics of the Upper Palaeozoic strata in YEB are closely related to the closure of the Paleo‐Asian Ocean (PAO). YEB underwent subduction‐related compression during the initial extensional phase of the fore‐arc basin from the Viséan to the Serpukhovian (late Early Carboniferous). During the Bashkirian–Sakmarian interval (Late Carboniferous to Early Permian), it was in subduction‐related fore‐arc and postarc rifting phases. During the Artinskian–Capitanian (Early‐Middle Permian) times, it was in an intracontinental rifting‐depression phase. During the Wuchapingian (Late Permian), it was in an intracontinental compressional phase. Tectonostratigraphy, tectonic evolution, and hydrocarbon potential assessments of the study area show that the Zhusileng Hangwula‐Tost Ul tectonic zone (ZHTUTZ) and southwestern part of Querrshan‐Atasbogd tectonic zone (QATZ) are identified as the main prospective areas for the exploration in the YEB. (b) According to the tectonostratigraphic analysis, tectonic evolution and hydrocarbon system of Carboniferous–Permian in the YEB, the YEB has similar attributes to the basin province in western CAOB (e.g., Santanghu and Junggar basins) and eastern CAOB (Erlian, Songliao Basin). To explore commercial oil and gas in the deeper strata (Carboniferous–Permian) of the eastern CAOB basins, further tectonostratigraphic analyses and comprehensive assessment on hydrocarbon potentials are necessitated in the near future.